Separation properties and fouling resistance of polyethersulfone membrane modified by fungal chitosan - Hilya N. Iman; Henry Susilo; Adhi Satriyatama; Ignatius D. M. Budi; Kiki A. Kurnia; I. G. Wenten; K. Khoiruddin (BMC Chemistry)
Abstract This research explores the enhancement of polyethersulfone (PES) membranes through the incorporation of chitosan derived from the lignicolous fungus Ganoderma sp. Utilizing wet phase inversion and solution casting techniques, chitosan was successfully integrated into the PES matrix, as confirmed by Fourier Transform Infrared Spectroscopy (FT-IR), which indicated a high deacetylation degree of 75.7%. The incorporation of chitosan significantly increased the membrane hydrophilicity, as evidenced by a reduction in the water contact angle and a substantial improvement in pure water permeability, from 17.9 L m-2 h-1 bar-1 to 27.3 L m-2 h-1 bar-1. The membrane anti-fouling properties were also notably enhanced, with the Flux Recovery Ratio (FRR) increasing from approximately 60–80%. Moreover, the chitosan-modified PES/CS membrane, particularly at a 5% chitosan concentration, demonstrated exceptional efficacy in pollutant removal, achieving over 90% elimination of total suspended solids, cadmium (Cd), and lead (Pb), alongside a 79% reduction in color during the treatment of textile wastewater.